Italian Robotic Antarctic Infrared Telescope (IRAIT) - TOSTI, Gino; BUSSO, Maurizio Maria; P. Maffei; S. Pascolini; L. Valenziano; M. Fiorucci; L. Corcione; M. Ferrari Toniolo; P. Persi (1997)
The Antarctic continent offers ideal atmospheric conditions to carry out observations at infrared wavelengths > 5 m, a task which is other wise possible only from space with rare and short-lived infrared satellites. In this paper we report the main characteristics of the Italian Robotic Infrared Telescope (IRAIT) which will be installed on the Antarctic Plateau. The telescope will be a f/20 Cassegrain with a 0.8-m parabolic primary mirror and an oscillating secondary mirror. It will be equipped with an IR-camera based on a Si:As or Si:Sb arrav of 128 × 128 pixels operating in the spectral range 8 - 27 m (Si:As) or 8 - 40 m (Si:Sb).